(untitled) (Tạp chí Y học Cộng đồng, 2025)
Abstract: Dengue fever (DF) remains a primary global health concern. High Fluorescence Lymphocyte Count (HFLC) reflects the immune response to infection by quantifying antibody-secreting cells (ASC), such as plasmablasts/plasma cells. ASCs are known to increase markedly in dengue compared to other febrile illnesses (OFIs). Objective: This study aimed to preliminarily evaluate the diagnostic value of HFLC in distinguishing dengue fever from other febrile illnesses. Methods: A cross-sectional study was conducted on 317 patients presenting with fever on admission. Clinical features and laboratory parameters, including HFLC# and HFLC%, were collected. Patients were categorized into the dengue infection (DI) group (n = 267) and the OFI group (n = 50). Results: The DI group had significantly higher median HFLC# (0.11 G/L) and HFLC% (5.2%) compared to the OFI group (0.01 G/L and 0.20%, respectively; p < 0.001). ROC analysis showed good diagnostic performance, with AUCs of 0.794 (HFLC#) and 0.842 (HFLC%). A cut-off value of 0.025 G/L for HFLC# yielded 70.4% sensitivity and 78.0% specificity. For HFLC%, a threshold of 0.75% resulted in 70.8% sensitivity and 88.0% specificity. Conclusion: HFLC demonstrates potential as a rapid and accessible marker for differentiating dengue fever from other febrile illnesses in clinical practice.